The Contribution of Yâdigâr-i Ibn-i Sharif to Orthopedics Through Fifteenth-Century Medical Knowledge: Modern Interpretations of Traditional Therapeutic Practices and an Ethnopharmacological–Orthopedic Analysis - Dinçel, Yaşar Mahsut; Adanır, Oktay; Kutluay, Gündüz Ercan (The European Research Journal, 2026)
This study examines the fifth chapter of Yâdigâr, written by the 15th-century Ottoman physician Tabîb Ibn-i Sharif, within the context of contemporary orthopedics and traumatology. The chapter addresses therapeutic approaches for musculoskeletal conditions, including fractures, dislocations, and contusions. The historical practices described in the text were interpreted in light of current biomedical and ethnopharmacological knowledge, with particular emphasis on herbal formulations and nutritional recommendations. Several of these traditional approaches suggest conceptual parallels with modern scientific understanding, especially regarding anti-inflammatory, antimicrobial, and nutritional effects that may support tissue healing. However, certain practices, such as bloodletting, are inconsistent with current orthopedic principles. Overall, this analysis indicates that historical medical texts such as Yâdigâr may provide conceptual rather than directly clinical relevance, offering valuable insights for ethnopharmacological research and contributing to a broader understanding of the historical development of orthopedic knowledge.